Mobilisations contre le gangstérisme et production d’une communauté morale coercitive en Afrique du Sud - Laurent Fourchard (European Journal of Turkish Studies)
Popular mobilizations against gangsters have been central in the social and political life of South African townships for decades. Yet this specific history does not tie in well with a narrative that would highlight a radical change from a politicized, militarized and repressive apartheid police, with a strong hostility to non-white populations, to a police less repressive, less politicized and more friendly with ‘historically disadvantaged’ people since the end of apartheid in 1994. This article draws on archival work, interviews with local leaders and police staff, participant observation in neighborhood watch patrols in poor neighborhoods of Cape Town, so as to understand the history of crime-fighting organizations and their relationship with the police - from cooperation to repression - before, during and after the period of apartheid. It reveals how these forms of mobilizations have been permeated by a multiplicity of individual choices: from partisan politics to the need for sociability, from a demand for more state intervention to the wish to police the neighborhood. It also reflects the inside violence of the organizations which participate in the production of a coercive social order, as implemented by parents and elders who perceived the youth as dangerous or as being in danger. These volunteers thus produced a moral community which, while fighting against the violence of gangsters and drug dealers in the townships, ultimately reproduced the generational gap inherited from the apartheid era.